2019
DOI: 10.1177/0265407519857155
|View full text |Cite
|
Sign up to set email alerts
|

Parent–child relationships following spousal/parental death: An application of relational turbulence theory

Abstract: The death of a family member is a difficult experience. Although implications of loss are felt on intra- and interpersonal levels, little is known about how it affects the relational functioning of surviving family members, and in particular the parent–child relationship. Using data collected from 144 bereaved parent–child dyads, this study examined how the divergent experiences of spousally bereaved parents and parentally bereaved children impact the parent–child relationship following spousal/parental death.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…They found that child self-competence was directly and negatively associated with discrepancies between child and parent reports of family functioning. Droser (2020) explored agreement in perceptions of relational uncertainty and interference from a partner in bereaved parent–child pairs. Discrepancies in reported type of uncertainty or interference from a partner between parents and children led to higher levels of experienced uncertainty and interference for parents.…”
Section: Work–family Conflictmentioning
confidence: 99%
“…They found that child self-competence was directly and negatively associated with discrepancies between child and parent reports of family functioning. Droser (2020) explored agreement in perceptions of relational uncertainty and interference from a partner in bereaved parent–child pairs. Discrepancies in reported type of uncertainty or interference from a partner between parents and children led to higher levels of experienced uncertainty and interference for parents.…”
Section: Work–family Conflictmentioning
confidence: 99%
“…To accomplish this, we used theoretical framing from the Relational Turbulence Theory (RTT). RTT provides a novel way to understand relationships in transition (Droser, 2020;Solomon & Brisini, 2019;Solomon & Knobloch, 2004;Solomon et al, 2016). The theory defines transition as a time when changing relationship status forces individuals to acclimate to new circumstances and roles (Solomon et al, 2016) such as that which occurs with the death of one partner.…”
Section: Purposementioning
confidence: 99%